Synthetic collagen mimics: self-assembly of homotrimers, heterotrimers and higher order structures - Fallas, Jorge A.; O'Leary, Lesley E. R.; Hartgerink, Jeffrey D. (Chemical Society reviews, 2010)
Collagen is a fascinating system of proteins that undergo a multi-step, hierarchical self-assembly which starts from individual peptide chains that assemble into a canonical triple helix. These triple helices then assemble into higher order structures which are often, but not always, fibrous in nature. While collagen is the most abundant protein in the human body, the details of its structure and mechanism of assembly are surprisingly poorly understood. This critical review will focus on small peptide systems, commonly referred to as collagen mimetic peptides (CMPs) which have been used successfully to help unravel some of the mystery of this complex structure. We will discuss homotrimeric CMPs, which are the most commonly researched subject in this field, and the structure of the collagen triple helix in detail and the factors that contribute to its stabilization. We will also cover how CMPs have been used to study breaks in triple helical domains as models for connective tissue diseases and, finally, how they have been used to understand the interactions of collagenous proteins with cell-surface receptors. Additionally, we will focus on heterotrimeric CMPs, a relatively new area of collagen research. Finally, we will deal with CMPs used as models for higher level self-assembly and also as materials that are designed to mimic the function of collagens in the extracellular matrix (178 references).